Організаційно-правові форми діяльності органів місцевого самоврядування - Кириченко, Ю. М.; Kyrychenko, Yu. M.; ORCID: http://orcid.org/0000-0001-9125-218X (Юридичний науковий електронний журнал. - 2022. - № 12. - С. 286-290, 2022)
Проаналізовано організаційно-правові форми діяльності органів місцевого самоврядування, серед яких виділено та охарактеризовано: сесії сільських, селищних, міських рад; засідання постійних комісій місцевих рад; засідання виконавчих комітетів сільських, селищних, міських рад; робота сільських, селищних, міських голів, старост; робота депутатів на всій території відповідної територіальної громади; організація і проведення місцевих референдумів, загальних зборів громадян; місцеві ініціативи членів територіальної громади; громадські слухання. Підкреслено, що основною організаційно-правовою формою роботи сільських, селищних, міських, районних у місті (у разі їх створення), районних, обласних рад є сесія – сукупність пленарних засідань ради, а також засідань її постійних комісій. Доведено, що все більшого розповсюдження набувають виїзні засідання постійних комісій відповідних рад, що сприяє активізації діяльності місцевих рад, а також дозволяє глибше вивчати проблеми, що турбують населення, та своєчасно їх вирішувати. До організаційної форми роботи посадових осіб органів місцевих рад віднесено роботу з населенням, що проявляється у двох формах: безпосередній (прийом громадян; розгляд звернень громадян; звіт посадових осіб перед територіальною громадою; інформування про свою діяльність через засоби масової інформації) та опосередкованій (через помічників, референтів, громадські приймальні, депутатський корпус, органи самоорганізації населення тощо).

The article provides a detailed analysis of the organizational-legal forms of local self-government bodies’ activity, among which the following are highlighted and characterized: sessions of local councils; meetings of standing commissions of local councils; meetings of executive committees of local councils; work of village, settlement, city heads, elders; work of deputies throughout the territory of the relevant territorial community; organization and holding of local referendums, general meetings of citizens; local initiatives of members of the territorial community; public hearings. It is emphasized that the main organizational-legal form of work of village, settlement, city, district in the city (if they are created), district, region councils is a session – a set of plenary meetings of the council, as well as meetings of its standing commissions. It has been proven that field meetings of the permanent commissions of the relevant councils are becoming more and more widespread, which contributes to the activation of the local councils activities’, and also allows for a deeper study of the problems that concern the population and their timely solution. The organizational form of work of local councils officials’ includes work with the population, which manifests itself in two forms: direct (reception of citizens; consideration of appeals from citizens; report of officials to the territorial community; informing about their activities through mass media) and indirect (through assistants , referents, public reception rooms, deputy corps, bodies of self-organization of the population, etc.). The set of organizational-legal forms of activity of local councils deputies’ is conditionally divided into the following groups: sessional and nonsessional, individual and collective, legal and organizational, forms of work in the local council and in the electoral district, etc. Particular attention is paid to such organizational and legal forms of implementation of functions and powers of the deputy at the session of the local council, as a deputy request and a deputy question. It has been established that the forms of direct participation of citizens in solving issues of local importance are local elections and referendum, general meetings of citizens at their place of residence, local initiatives of members of the territorial community; public hearings, bodies of selforganization of the population, the implementation of which requires improvement and the introduction of appropriate changes to the current legislation of Ukraine.

Проанализированы организационно-правовые формы деятельности органов местного самоуправления, среди которых выделены и охарактеризованы: сессии сельских, поселковых, городских советов; заседание постоянных комиссий местных советов; заседания исполнительных комитетов сельских, поселковых, городских советов; работа сельских, поселковых, городских голов, старост; работа депутатов на всей территории соответствующего территориального общества; организация и проведение местных референдумов, общего собрания граждан; местные инициативы членов территориального общества; публичные слушания.
Organizational-legal forms of the local self-government bodies’ activity
Кириченко, Ю. М. Організаційно-правові форми діяльності органів місцевого самоврядування [Електронний ресурс] / Кириченко Ю. М. // Юридичний науковий електронний журнал. - 2022. - № 12. - С. 286-290. - Режим доступу: http://lsej.org.ua/12_2022/66.pdf.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; органи місцевого самоврядування; local governments; органы местного самоуправления; організаційно-правові форми; organizational and legal forms; организационно-правовые формы; сесія місцевої ради; local council session; сессия местного совета; посадова особа; official; должностное лицо; міський голова; city mayor; староста; headman; органи самоорганізації населення; bodies of self-organization of the population; органы самоорганизации населения